ESG Funds versus traditional funds: a performance analysis in the brazilian market (from 2021 to 2024) - Abreu, Júlia Gomes Ramos; Ribeiro, Cíntia de Melo de Albuquerque; Silva, Aline Moura da Costa; Cosenza, José Paulo (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To examines the performance differences between Environmental, Social and Governance (ESG) and traditional funds in the Brazilian market, using risk-adjusted return measures. Methodology: A quantitative approach was used, with secondary data from the Brazilian Securities Commission on the returns of 3,538 investment funds from 2006 to 2026. The Sharpe Ratio and t-test were applied to address this objective. Results: In the graphical analysis, ESG funds showed better performance and higher volatility than non-ESG funds. However, the Student’s t-test showed that these differences are not statistically significant. Thus, there is insufficient evidence to say that the two portfolios perform differently in a statistically meaningful way. Contributions: This study contributes to the academic and practical debate on sustainable investments, providing insights for investors, fund managers, and policymakers seeking to balance financial returns with socio-environmental responsibility.